1988
DOI: 10.1021/la00079a027
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of benzene, cyclohexene, and cyclohexane with the surface of titanium dioxide (rutile)

Abstract: 147sols containing particles with diameters well below 0.01 pm. Very small particle sizes are accessible because these materials have high densities (10.5 and 19.3 g/cm3 for silver and gold), and retention in SFFF depends on particle mass.The high extinction efficiencies of these small particles makes detection by optical means practical, even at sample concentrations as low as the 0.005% of the gold sol described here.The silver and gold sols which we have examined are easily dispersed in dilute aqueous FL-70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…Two distinct adsorption mechanisms were proposed for ethanol on TiO 2 prior to photocatalytic oxidation: non-dissociative hydrogenbonding to surface OH species, and dissociative adsorption at oxygen bridging sites. [41,42] Oxygenated compounds containing an aromatic ring are believed to adsorb through both, p-bonding of the aromatic ring to exposed titanium cations [43,44] and hydrogen-bonding with oxygen bridging sites. The existence of different types of sites has been confirmed by the finding that the photoreaction selectivity may be affected by adding a suitable hole trap [23] or by poisoning a certain type of site.…”
Section: Partial Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two distinct adsorption mechanisms were proposed for ethanol on TiO 2 prior to photocatalytic oxidation: non-dissociative hydrogenbonding to surface OH species, and dissociative adsorption at oxygen bridging sites. [41,42] Oxygenated compounds containing an aromatic ring are believed to adsorb through both, p-bonding of the aromatic ring to exposed titanium cations [43,44] and hydrogen-bonding with oxygen bridging sites. The existence of different types of sites has been confirmed by the finding that the photoreaction selectivity may be affected by adding a suitable hole trap [23] or by poisoning a certain type of site.…”
Section: Partial Oxidationmentioning
confidence: 99%
“…[29] In the glycerol structure, differently from aromatic alcohols, three OH groups are present, and consequently adsorption and desorption of reagents and products occur to a different extent and with different strength. [29,42,43] Product A at m/ z = 176 could derive from two molecules of glyceric acid strongly adsorbed onto the surface. The findings that glyceric acid is absent from the solution and that the pH value does not vary in the course of the runs support the hypothesis that undissociated glyceric acid is not able to desorb from the TiO 2 surface, thus probably generating product A.…”
Section: Aliphatic Alcoholsmentioning
confidence: 99%
“…17 Moreover, it is known that benzene molecules adsorb onto titania through a Ti-OHÁ Á Áp interaction at hydroxylated or a Ti 4+ Á Á Áp interaction at dehydroxylated surfaces. 18,19 Hence, under visible light irradiation, weak sub-bandgap transitions from the surface states to the conduction band of TiO 2 are possible.…”
mentioning
confidence: 99%
“…In the case of the hydroxylated surface, the pi system of benzene would be expected to interact with the hydrogen in the hydroxyl on the surface. This interaction has been suggested to occur between benzene and hydroxyl groups present on alumina [30] and titania surfaces [31]. Theoretical calculations have shown that hydrogen-bonding interactions are predominant in benzene-water systems [32].…”
Section: Discussionmentioning
confidence: 99%